Level I PD‐MCI Using Global Cognitive Tests and the Risk for Parkinson's Disease Dementia. Issue 4 (29th April 2022) - Boel, Judith A.; de Bie, Rob M.A.; Schmand, Ben A.; Dalrymple‐Alford, John C.; Marras, Connie; Adler, Charles H.; Goldman, Jennifer G.; Tröster, Alexander I.; Burn, David J.; Litvan, Irene; Geurtsen, Gert J.; ,
ABSTRACT: Background: The criteria for PD‐MCI allow the use of global cognitive tests. Their predictive value for conversion from PD‐MCI to PDD, especially compared to comprehensive neuropsychological assessment, is unknown. Methods: The MDS PD‐MCI Study Group combined four datasets containing global cognitive tests as well as a comprehensive neuropsychological assessment to define PD‐MCI (n = 467). Risk for developing PDD was examined using a Cox model. Global cognitive tests were compared to neuropsychological test batteries (Level I&II) in determining risk for PDD. Results: PD‐MCI based on a global cognitive test (MMSE or MoCA) increases the hazard for developing PDD (respectively HR = 2.57, P  = 0.001; HR = 4.14, P  = <0.001). The C‐statistics for MMSE (0.72) and MoCA (0.70) were lower than those based on neuropsychological tests (Level I = 0.82; Level II = 0.81). Sensitivity, specificity and diagnostic accuracy balance was best in Level II. Conclusion: MMSE and MoCA predict conversion to PDD. However, Level II neuropsychological assessment seems the preferred assessment for PD‐MCI.